2015
DOI: 10.1186/s12905-015-0179-0
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of transcervical hysteroscopic endometrial resection based on the prevention of the recurrence of endometrial polyps in post-menopausal women

Abstract: BackgroundThe objectives of this study were to determine the effectiveness the effectiveness of post-polypectomy hysteroscopic endometrial resection in preventing the recurrence of endometrial polyps in post-menopausal patients and analyse the complications and necessity of additional surgery in patients, in addition to their degree of satisfaction.MethodsA prospective longitudinal study of post-menopausal patients diagnosed with endometrial polyps was conducted including polypectomy and hysteroscopic endometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Recurrence of endometrial polyps after polypectomy depends on the technique used for polyp removal, experience of the surgeon, as well as the characteristics of the polyps and patients [17]. While some authors found a low rate of recurrence even after several years of monitoring patients, other studies have recorded the recurrence rate as high as 50% [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Recurrence of endometrial polyps after polypectomy depends on the technique used for polyp removal, experience of the surgeon, as well as the characteristics of the polyps and patients [17]. While some authors found a low rate of recurrence even after several years of monitoring patients, other studies have recorded the recurrence rate as high as 50% [18,19].…”
Section: Discussionmentioning
confidence: 99%